The production of carbon dioxide from carbon monoxide and oxygen sensitized by photolysis of bis (PERFLUOROMETHYL)Peroxide - Blesa, Miguel Ángel; Aymonino, Pedro J. (Asociación Química Argentina, 1971)
Fil: Blesa, Miguel Ángel Comisión Nacional de Energía Atómica; Argentina